Fenomena Keterlantaran Suku Baduy di Pulau Jawa - Stephanus Ngamanken (Humaniora, 2013)
Baduy  is a tribe that applies isolation from the outside world. They are not familiar with school, because school as formal education is opposed to their lifestyle. This study aims to explain the background and development of Baduy people whom are neglected, marginalized, and overlooked despite they live in Java island. The research method used is descriptive, case study type. The case is about why the Baduy tribe is neglected, marginalized, and overlooked. The Baduy tribe lives in Kanekes village, 39 km from Rangkasbitung city, 120 km from Jakarta. Data collecting uses interview and observation from January 2012 to June 2013. Data analysis uses qualitative data analysis technique. The results show five phenomena in the origin and development of the people which lead them to be neglected, marginalized, and overlooked. This study leads to conclusion that Baduy people need humanitarian assistance; and Paulo Freire’s conscience is one of the alternatives in providing humanitarian assistance to them.